About some changes in the kinship system of Khorchin Mongols (Өvөr Mongolyn Tunlyao hotyn Horchin Zүүn garyn dund hoshuuny shibahua balgasny Bayantaria gacaany zhisheegeer) - Huyagt Ch. Munkhtor (Nomadic Civilization: Historical Research, 2024)
This article was written by the author based on the original materials of the field research conducted in 2015-2017 at the Shibahua Ruins Bayantaria Gorge, Horqing Left Hand Cape, Tongliao City, China’s National Autonomous Region. The article will talk about the kinship system and the change in the pronunciation of the relatives of the Khorchin Mongols, who are engaged in farming in the eastern part of the Republic of Kazakhstan, and have been greatly influenced by Chinese culture. Genealogy and kinship systems are very difficult to define and are very interesting objects of study. The systematization of the material in the most formal description is a matter for the more distant future. This time, the author made a tripartite conclusion about the meaning and capabilities of the kinship system (1. Fear of belonging; 2. Rights and responsibilities; 3. Activity) about the meaning and capabilities of the kinship system, which was evaluated by the researchers. tried to analyze the problem of understanding and being a model of what is understood in understanding) on the example of Khorkhin Mongols. In order to make the article understandable to all readers, the diagram of the kinship system of Inner Mongolia in the first half of the 20th century is included alongside the diagram of the kinship system of the present day.